1965
DOI: 10.1002/jsfa.2740160602
|View full text |Cite
|
Sign up to set email alerts
|

The search for a veterinary insecticide. I.—Sulphonamides and disulphonamides active against sheep blowfly

Abstract: Laboratory and field test methods are described for assessing the activity of chemicals for the control of sheep blowfly Luciliu sericatu (Meig.). The essential properties for a sheep blowfly insecticide are discussed. Screening results for several series of sulphonamides and disulphonamides, with and without N-substituents, are presented. Although some disulphonamides showed high activity, none had the necessary persistence for use in a sheep-dip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1967
1967
1980
1980

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Consequently, it may also be speculated that Sarnorin has some potentials for vector control just as sulphonamides were shown to have potentials for controlling the larvae of the blow fly, Lucilia sericata (Greenwood and Harrison, 1965), mosquitoes (Eddy et aI, 1965) and R. prolixus (Musgrave and French, 1969).…”
Section: Rate Of Emergence and Sex Ratios Of Emergent Fliesmentioning
confidence: 99%
“…Consequently, it may also be speculated that Sarnorin has some potentials for vector control just as sulphonamides were shown to have potentials for controlling the larvae of the blow fly, Lucilia sericata (Greenwood and Harrison, 1965), mosquitoes (Eddy et aI, 1965) and R. prolixus (Musgrave and French, 1969).…”
Section: Rate Of Emergence and Sex Ratios Of Emergent Fliesmentioning
confidence: 99%
“…Screening of potential insecticides has usually been done with larvae, since these are the normal target of the insecticides. [1][2][3][4] In contrast, investigations of insecticide resistance in these insects have formerly employed adult insects, presumably on grounds of convenience. [5][6][7] Recently, however, two slightly different methods of measuring resistance in Australian sheep blowflies, employing first stage larvae, have been prop0sed;8?~ using such tests, it has been shown that resistance levels in the adult bear no definite relation to those in the larva.9 This finding raises several problems, since the techniques employed in tests with adults or larvae were so different.…”
Section: Introductionmentioning
confidence: 99%
“…In early fly strikes, larvae of Lucilia abrade the skin and feed mainly on the exuding serum. Blood serum has therefore often been employed in larvicide tests against young larvae, with either wool or cotton wool to absorb the serum and toxicant (Hobson, 1937;Du Toit & Fiedler, 1953;Harrison & Johnson, 1961;Greenwood & Harrison, 1965;Shaw & Blackman, 1971). In Queensland this technique is used for testing third-instar larvae of L. cuprina, 48 h old (P.J.…”
Section: Introductionmentioning
confidence: 99%